Attractors for infinite-dimensional non-autonomous dynamical systems - Carvalho, Alexandre; Langa, José A.; Robinson, James; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
This book treats the theory of pullback attractors for non-autonomous dynamical systems. While the emphasis is on infinite-dimensional systems, the results are also applied to a variety of finite-dimensional examples.   The purpose of the book is to provide a summary of the current theory, starting with basic definitions and proceeding all the way to state-of-the-art results. As such it is intended as a primer for graduate students, and a reference for more established researchers in the field.   The basic topics are existence results for pullback attractors, their continuity under perturbation, techniques for showing that their fibres are finite-dimensional, and structural results for pullback attractors for small non-autonomous perturbations of gradient systems (those with a Lyapunov function).  The structural results stem from a dynamical characterisation of autonomous gradient systems, which shows in particular that such systems are stable under perturbation. Application of the structural results relies on the continuity of unstable manifolds under perturbation, which in turn is based on the robustness of exponential dichotomies: a self-contained development of  these topics is given in full. After providing all the necessary theory the book treats a number of model problems in detail, demonstrating the wide applicability of the definitions and techniques introduced: these include a simple Lotka-Volterra ordinary differential equation, delay differential equations, the two-dimensional Navier-Stokes equations, general reaction-diffusion problems, a non-autonomous version of the Chafee-Infante problem, a comparison of attractors in problems with perturbations to the diffusion term, and a non-autonomous damped wave equation. Alexandre N. Carvalho is a Professor at the University of Sao Paulo, Brazil. José A. Langa is a Profesor Titular at the University of Seville, Spain. James C. Robinson is a Professor at the University of Warwick, UK.
The pullback attractor -- Existence results for pullback attractors -- Continuity of attractors -- Finite-dimensional attractors -- Gradient semigroups and their dynamical properties -- Semilinear Differential Equations -- Exponential dichotomies -- Hyperbolic solutions and their stable and unstable manifolds -- A non-autonomous competitive Lotka-Volterra system -- Delay differential equations.-The Navier–Stokes equations with non-autonomous forcing.-  Applications to parabolic problems -- A non-autonomous Chafee–Infante equation -- Perturbation of diffusion and continuity of attractors with rate -- A non-autonomous damped wave equation -- References -- Index.-.
Keywords: Partial differential equations; Dynamics; Ergodic theory; Manifolds (Mathematics).; Complex manifolds; Partial Differential Equations; Dynamical Systems and Ergodic Theory; Manifolds and Cell Complexes (incl. Diff.Topology).